effect of Ethanol on the kidney of the white rat Rattus norvegicus followed by treatment with camel milk (histological study) - Mahmood Nawfel Mustafa; Aziz Khaled Hameed (Tikrit Journal of Pure Science, 2023)
This study was designed to identify the influence of alcohol in the inducing histological lesions in the kidney of  white rats and the possibility of treating these effects by using camel milk. In this study ,12 rats were used and randomly divided into three groups each group contained four animals, the first group was control group had been fed by usual diet and administrated by distilled water, second and third groups administrated by ethanol for 3 months (a dose began at 10% v / v / day and gradually increase to up to 15% v / v / day), then Group C were treated by camel milk with open dose for one month , the results of the current study, showed that the second group occurrence of a number of histopathological lesions in the kidney tissue represented by infiltration of lymphocytes with the occurrence of fibrosis within the overall tissues and thickening walls of the blood vessels in addition to the destroyed of some glomeruli and desquamation of the lining epithelial of proximal and distal tubules and destroyed of others , and accumulation of hyaline crystals in lumen of others, As for the third group it had been observed most of the kidney tissues returned to a semi-natural state.